Facial reconstruction using polypropylene mesh after resection of maxillary ossifying fibroma - R. Soesanto (Dental Journal (Majalah Kedokteran Gigi), 2012)
Background: Ossifying fibroma is a variant of fibrous dysplasia and catagorized as osteofibrosis lesion. It commonly affects long bones but occasionally involves jaws. Mandible affected more common than maxilla. The treatment of ossifying fibroma include excision and resection. Excision of lesion and resection of maxilla could cause facial defect which cannot be reconstructed with bone graft. Purpose: The aim of this case report is to report the potential use of polypropylene mesh in facial reconstruction after hemimaxillectomy in patients diagnosed with ossifying fibroma of the maxilla. Case: A 17-years-old female patient came to Oral and Maxillofacial Surgery clinic, Dental Hospital, Faculty of Dentistry, Airlangga University, with chief complaint of swelling in the upper left cheek of 2 years duration which was not related to any history of toothache. Patient also complained of the itchiness and pain on the swelling area occasionally as well as salty discharge from the mass. The FNA was done and the citology result indicated a benign mesenchimal tumor. Incisonal biopsy was subsequently performed and the histopathology report confirmed the diagnosis of cementifying fibroma. Case management: Left hemimaxillectomy was done, and post surgical defect in the facial and buccal aspect was immediately reconstructed using three layers of polypropylene mesh. On follow-up, eleven months post-operatively, the patient was well and there was no facial deformity or asymmetry. Conclusion: Polypropylene mesh is a potential material for facial reconstruction as it can reduce the risk of facial deformity after hemimaxillectomy of patients with tumor of the maxilla.Latar belakang: Ossifying fibroma merupakan varian dari fibrous dysplasia dan termasuk di dalam kategori lesi osteofibrosis. Umumnya mengenai tulang panjang tetapi dapat juga mengenai rahang dan lebih banyak menyerang tulang mandibula dibanding maksila. Perawatan ossifying fibroma dilakukan dengan eksisi atau reseksi. Perawatan eksisi atau reseksi tulang maksila dapat mengakibatkan deformitas wajah yang tidak dapat direkontruksi dengan bone graft. Tujuan: Laporan kasus ini bertujuan untuk melaporkan penggunaan polipropylene mesh pada rekonstruksi wajah setelah hemimaxillectomy pada pasien dengan diagnose ossifying fibroma pada maksila. Kasus: Penderita wanita berusia 17 tahun datang ke Klinik Bedah Mulut dan Maksilofasial, Rumah Sakit Gigi dan Mulut Fakultas Kedokteran Gigi Universitas Airlangga, dengan keluhan utama pembengkakan pada pipi kiri atas yang muncul sejak 2 tahun yang lalu tanpa ada riwayat keluhan sakit gigi. Penderita mengeluh gatal, kadang sakit dan keluarnya cairan asin pada daerah benjolan. Hasil FNA dan test sitologi menunjukkan gambaran tumor jinak mesensimal. Pemeriksaan dengan biopsi dan histopatologi mengkonfirmasi diagnosa cementifying fibroma. Tatalaksana kasus: Dilakukan hemimaksilektomy pada sebelah kiri, dan defek pasca pembedahan pada sisi fasial dan bukal segera direkontruksi dengan pemasangan polipropylene mesh 3 lapis. Sebelas bulan setelah operasi kondisi pasien baik dan tidak ada deformitas atau asimetri wajah. Kesimpulan: Polypropylene mesh merupakan bahan yang potensial untuk rekonstruksi wajah karena dapat mengurangi terjadinya deformitas wajah setelah hemimaxillectomy pada pasien dengan tumor maksila.